Clinical and economic consequences of pancreatic fistula after elective pancreatic resection - Čečka, Filip; Jon, Bohumil; Šubrt, Zdeněk; Ferko, Alexander (Hepatobiliary & pancreatic diseases international, 2013)
BACKGROUND: Postoperative pancreatic fistula is the main cause of morbidity after pancreatic resection. This study aimed to quantify the clinical and economic consequences of pancreatic fistula in a medium-volume pancreatic surgery center. METHODS: Hospital records from patients who had undergone elective pancreatic resection in our department were identified. Pancreatic fistula was defined according to the International Study Group on Pancreatic Fistula (ISGPF). The consequences of pancreatic fistula were determined by treatment cost, hospital stay, and out-patient follow-up until the pancreatic fistula was completely healed. All costs of the treatment are calculated in Euros. The cost increase index was calculated for pancreatic fistula of grades A, B, and C as multiples of the total cost for the no fistula group. RESULTS: In 54 months, 102 patients underwent elective pancreatic resections. Forty patients (39.2%) developed pancreatic fistula, and 54 patients (52.9%) had one or more complications. The median length of hospital stay for the no fistula, grades A, B, and C fistula groups was 12.5, 14, 20, and 59 days, respectively. The hospital stay of patients with fistula of grades B and C was significantly longer than that of patients with no fistula (P<0.001). The median total cost of the treatment was 4952, 4679, 8239, and 30 820 Euros in the no fistula, grades A, B, and C fistula groups, respectively. CONCLUSIONS: The grading recommended by the ISGPF is useful for comparing the clinical severity of fistula and for analyzing the clinical and economic consequences of pancreatic fistula. Pancreatic fistula prolongs the hospital stay and increases the cost of treatment in proportion to the severity of the fistula.
Keywords: ambulantní péče; Pancreatectomy; pankreatektomie; Humans; lidé středního věku; Female; Aged; Time Factors; výsledek terapie; Costs and Cost Analysis; senioři; lidé; nemocnice - náklady; náklady a analýza nákladů; časové faktory; Pancreatic Fistula; Ambulatory Care; Elective Surgical Procedures; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; pankreatická píštěl; Treatment Outcome; Severity of Illness Index; Hospital Costs; elektivní chirurgické výkony; mužské pohlaví; Length of Stay; délka pobytu